Understanding the patterns of PPP renegotiations for infrastructure projects in Latin America: The case of Brazil. Issue 3 (September 2017) - Neto, Dimas de Castro e Silva; Cruz, Carlos Oliveira; Sarmento, Joaquim Miranda
The increased use of public–private partnerships (PPPs) around the world to build infrastructures and provide public services has led to several concerns. One of the main pitfalls of PPPs is an abnormal frequency of renegotiations, especially renegotiations occurring during the first years of contract. The Latin American experience has been the most relevant in terms of research on PPP renegotiations. Using the literature on PPP renegotiations in the Latin American context, this article focuses on the analysis and discussion of renegotiations. We use the experience from Brazil, at the State (region) level, of PPPs and renegotiations. From 2006 to 2016, Brazil developed 42 PPP projects in several sectors. From these, 27 were renegotiated at least once. We found a high number of renegotiations within a short period since the start of the contract for the first renegotiation to occur. The motives for renegotiations are mainly perceived from the public sector, particularly failure in planning, concept, and bidding. Electoral periods and the political connections of shareholders also have an impact on renegotiations. Based on the Brazilian experience, we drawn some policy implications.